KKN UMD 174 Universitas Jember Menggagaskan Kegiatan Bank Sampah di Desa Condro - Intan Zahra Hartika; Nur Akdiahtul Jhannah; Sigit Prastowo (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Garbage has become a national problem and a very important issue in the environment. In essence, waste will not decrease or run out, in fact it will continue to increase along with the increase in population. In the waste collection system in both RTs, each household provides a sack or trash bag as a place for collecting plastic waste. Plastic waste that has been collected for 1-2 weeks will be exchanged with waste collectors who have collaborated at the waste bank post in each RT. It is hoped that the establishment of a waste bank can help reduce the amount of waste that is disposed of in landfills. Waste that can be recycled will be sorted and processed further.